Trophic transfer of hexabromocyclododecane in the terrestrial and aquatic food webs from an e-waste dismantling region in East China - Zhu, Chaofei; Wang, Pu; Li, Yingming; Chen, Zhaojing; Li, Honghua; Ssebugere, Patrick; Zhang, Qinghua; Jiang, Guibin (Environmental Science, 2017)
Trophic transfer of hexabromocyclododecane (HBCD) was investigated in both the terrestrial and aquatic food webs from an e-waste dismantling region in East China. The mean S3HBCD concentrations in the terrestrial species varied from 0.91 (0.16–1.85) ng g 1 lipid weight (lw) in dragonflies (Pantala flavescens) to 40.3 (22.1–51.1) ng g 1 lw in rats (Rattus norvegicus). The isomeric profile indicated that a-HBCD presented a decreasing trend along the trophic level (TL) (from 97.2% to 16.3% of S3HBCDs), while g-HBCD showed a reverse trend (from 2.8% to 73.6% of S3HBCDs). The trophic magnification factor (TMF) derived from the slope of the regression line between TLs and ln-transferred S3HBCDs was 0.10, suggesting a trophic dilution of HBCD in the terrestrial food web. By contrast, in the aquatic species, S3HBCD concentrations varied from 5.02 (3.5–6.55) ng g 1 lw in apple snails (Ampullaria gigas spix) to 45.9 (14.9–67.8) ng g 1 lw in grass carps (Ctenopharyngodon idellus). a-HBCD was the dominant isomer, followed by g-HBCD in the majority of species. A positive linear relationship was observed in the plots of ln S3HBCDs versus TLs (R2 ¼ 0.81, p ¼ 0.06). The TMF for S3HBCDs was 6.36, indicating a trophic magnification of HBCD in the aquatic food web. Although these results demonstrated the distinct trophic transfer of S3HBCDs in different ecosystems, further research is needed to eliminate the uncertainty of the tendencies, due to the non-significant relationship and limited species.
Keywords: Trophic transfer; Hexabromocyclododecane; Terrestrial and aquatic food webs; e-waste dismantling region